Price floors for emissions trading - Peter John Wood; Frank Jotzo (Fondazione Eni Enrico Mattei (FEEM), 2009)
Price floors in greenhouse gas emissions trading schemes can have advantages for technological innovation, price volatility, and management of cost uncertainty, but implementation has potential pitfalls. We argue that the best mechanism for implementing a price floor is to have firms pay an extra fee or tax. This has budgetary advantages and is more compatible with international permit trading than alternative approaches that dominate the academic and policy debate. The fee approach can also be used to implement more general hybrid approaches to emissions pricing.
Keywords: Q58; 330; Price Floor; Price Ceiling; Carbon Tax; Emissions Trading; Carbon Pricing; Price and Quantity Controls; Waxman-Markey Bill